Level of acquisition of skills for care in nursing hospital inmates, Lambayeque 2020 - Alarcón Vigil, Gabriela Belén (2021)
Objective: To determine the level of acquisition of skills for care in nursing hospital interns, Lambayeque 2020. Method: Quantitative approach, simple descriptive. Population made up of 132 nursing interns. A Likert scale was applied as an instrument, which evaluated the level of acquisition of skills for care, consisting of two dimensions with 21 items, which was subjected to tests of validity, consistency and reliability, with the analysis of expert judgment through the test binomial, reaching the conclusion the proportion of questions accepted by judge N ° 1, 2,3 for the instrument is equal to 85%, which is an acceptable value and applying a pilot test, using the statistical program SPSS 25, the validity, obtaining a Cronbach's alpha of 0.672, which indicates that there is a good and adequate reliability. The criteria of scientific rigor (internal and external validity) and ethical principles (authenticity, autonomy, non-maleficence and justice) were taken as a basis. The data were processed with the SPSS 25 program. Results: 75.8% stated that their acquisition of skills was very good during their hospital stay and 0.8% thought it was not. In the beginner and advanced beginner dimensions, a very good level of skill acquisition was obtained with 64.4% and 81.8% respectively. Conclusion: the acquisition of skills was very good because the students recognized their pre-professional practices as an opportunity to achieve competencies with constant practice in the different services. Keywords: Skills acquisition, nursing internship, nursing care. Decs Terms: Skill (F02.784.629.131), Care (F01.752.355), Nursing (H02.478).